Surface modification of stainless steel 316L by using pulsed laser - Phuah, Yong Zhen (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this study is to decrease the production leadtime on curing processthat producing catheter tube in Company XYZ in order to fulfill the high demand on hospital as a medical device. In order to effectively conduct on curing process improvement, current process performance must be well understood and measurable. Then, by using Lean tool and techniques effectively, the productions lead time on curing process can be reduce hopely.Therefore, the current curing process in that company has a waste of time by waiting each process to another process.